Performance Analysis of the Pharmacy Installation Dr Harjono Ponorogo Regional General Hospital in 2023 Based on the Balanced Scorecard Method - Yustyananingrum, Nora; Wijayanti, Tri; Harsono, Samuel Budi (MEDFARM: Jurnal Farmasi dan Kesehatan, 2025)
Background: RSUD Dr. Harjono Ponorogo is a referral health facility in the Ponorogo district. So far, its performance measurement has only focused on financial aspects. Therefore, a more comprehensive approach is needed using the Balanced Scorecard method which includes four main perspectives, namely financial perspectives, internal business processes, customers, growth and learning Objectives: To determine the performance of IFRS RSUD dr Harjono balanced scorecard method using four perspectives. Methods: Descriptive research method with a combination approach involved all IFRS employees and repeat visit outpatients, this study designed non-experimental case study was descriptive. Data collected in the form of quantitative data and qualitative. The sampling technique used was purposive sampling. Criteria used for the respondent customers are all Hospital Pharmacy Installation employees and repeat visit outpatients Results: The results showed on Financial perspective suggests that ITOR in 2022 was 12,90 and 2023 was 10,91, GPM in 2022 was 19,69% and 2023 was 19,68%, GROS in 2022 was growth 1,25% and 2023 was growth 1,52%. Internal Business Processes perspective suggests that was availability of drugs according to standards However, the value of dead stock drugs at 4.86% and expired drugs at 1.96% is still above the standard value of more than 1%. The results showed on Customers on five dimensions still obtained negative result an average GAP of -0.54 his shows that the IFRS RSUD Dr Harjono provides unsatisfactory service quality for patients. In the perspective of growth and learning, the ability and motivation to work are in a very high category Conclusion: Financial perspective, internal business processes, growth and learning in the good category and according to standards except for the dead stock and Expired Date values still above the standard. In the customer perspective, they are still dissatisfied with the service, so the pharmaceutical installation requires an improvement strategy